THE CHOICE OF A METHOD FOR SURGICAL TREATMENT OF INTERNAL CHRONIC HEMORRHOIDS - Kravtsiv, M.I.; Dudchenko, M.O.; Ivashchenko, D.M.; Prykhidko, R.A.; Shevchuk, M.P.; Zaiets, S.M.; Ivanova, G.O. (World of Medicine and Biology, 2022)
Haemorrhoids are one of the most common diseases in the anorectal zone. Often this disease requires surgical treatment, so the study of types of operations for treatment of hemorrhoids is very important in our time. The aim of our study was to compare Rafaelo radiofrequency ablation of hemorrhoids and Milligan-Morgan hemorrhoidectomy to determine the best method of surgical treatment of chronic hemorrhoids. Our study included 135 patients divided into two groups. The first group consisted of 75 patients operated on by radiofrequency ablation, the second group consisted of 60 patients who underwent classical Milligan-Morgan hemorrhoidectomy. Obtained results showed that the method of radiofrequency ablation of hemorrhoids using the Rafaelo method is less traumatic, easier to perform for surgeons, has an insignificant level of postoperative pain, low frequency of early and late postoperative complications and recurrence, does not require additional drug therapy and is characterized by a short postoperative period and recovery.
Keywords: internal hemorrhoids; radiofrequency ablation; hemorrhoidectomy; Milligan-Morgan; Rafaelo